REVITALISASI MUSEUM MANUSIA PURBA GILIMANUK - Ida Ayu Gede Megasuari Indria (Balai Arkeologi Bali, 2016)
Revitalization of the Ancient Man Museum of Gilimanuk is very important to do as a first step to establish better communication between the museum and the community it serves. This study aims to describe the revitalization performed at the Ancient Man Museum of Gilimanuk and its relation to the strengthening of national identity. Data collection was conducted through observation, interview, and literature study. Data analysis in this research was conducted using qualitative analysis through descriptive technique and philosophical approach. The result shows that the revitalization performed at the Ancient Man Museum of Gilimanuk includes updating the interior of the main exhibit hall and also a site museum arrangement in accordance with the concept of the new museum. The revitalization at the Ancient Man Museum of Gilimanuk can increase the public awareness of their cultural identity. Revitalisasi sangat penting dilakukan sebagai langkah awal untuk membangun komunikasi yang lebih baik antara Museum Manusia Purba Gilimanuk dan masyarakat yang dilayani. Penelitian ini bertujuan untuk mendeskripsikan revitalisasi yang dilakukan di Museum Manusia Purba Gilimanuk dan kaitannya dengan penguatan identitas bangsa. Metode pengumpulan data dalam penelitian ini adalah observasi, wawancara, dan studi kepustakaan. Pengolahan data dalam penelitian ini menggunakan analisis kualitatif dengan teknik deskriptif dan pendekatan filosofis. Hasil penelitian menunjukkan bahwa revitalisasi yang dilakukan di Museum Manusia Purba Gilimanuk meliputi pembaharuan interior ruang pameran utama dan juga penataan ruang site-museum sesuai dengan konsep new museum. Adanya revitalisasi di Museum Manusia Purba Gilimanuk dapat berpengaruh pada meningkatnya kesadaran masyarakat akan identitas budayanya.